Vasomotor dysfunction in patients with angina and nonobstructive coronary artery disease is dominated by vasospasm. (15th June 2021) - Konst, Regina E.; Damman, Peter; Pellegrini, Dario; Hartzema-Meijer, Mariëlle J.; van Uden, Bas J.C.; Jansen, Tijn P.J.; Brandsma, Judith; Vart, Priya; Gehlmann, Helmut; Maas, Angela H.E.M.; van Royen, Niels; Elias-Smale, Suzette E.
Abstract: Background: Coronary vasomotor dysfunction, comprising endotypes of coronary spasm and/or impaired microvascular dilatation (IMD), is common in patients with angina and no obstructive coronary arteries (ANOCA). However, there are discrepant reports regarding the prevalence of these endotypes. The objective of this study was to determine the prevalence of coronary vasomotor dysfunction in patients with ANOCA, underlying endotypes, and differences in clinical characteristics. Methods: Prospective registry of patients with ANOCA that underwent clinically indicated invasive coronary function testing (CFT), including acetylcholine spasm testing (2–200 μg) to diagnose coronary spasm, and adenosine testing (140 μg/kg/min) to diagnose IMD, defined as an index of microvascular resistance ≥25 and/or coronary flow reserve <2.0. Results: Of the 111 patients that completed CFT (88% female, mean age 54 years), 96 (86%) showed vasomotor dysfunction. The majority 93 (97%) had coronary spasm, 63% isolated and 34% combined with IMD. Isolated IMD was rare, occurring in only 3 patients (3%). Hypertension was more prevalent in patients with vasomotor dysfunction compared to those without (39% vs. 7%, p  = 0.02). Obesity and a higher severity of angiographic atherosclerotic disease were more prevalent in patients with coronary spasm compared to those without (61% vs. 28%; 40% vs. 0%, respectively, both p  < 0.01). No differences in angina characteristics were observed between patients with and without vasomotor dysfunction or between endotypes. Conclusions: Coronary vasomotor dysfunction is highly prevalent in patients with ANOCA, especially epicardial or microvascular vasospasm, whereas isolated IMD was rare. Performing a CFT without acetylcholine testing should be strongly discouraged. Graphical abstract: Patients with signs and symptoms of Angina and No Obstructive Coronary Artery Disease and the diagnostic yield of a Coronary Function Test. CFR = coronary flow reserve; IMR = index of microvascular resistance. Unlabelled Image